Understanding the Context for Agricultural Technical, Vocational, Education and Training in Haiti - M. Christelle Calixte; T. Grady Roberts; J. C. Bunch (Journal of International Agricultural and Extension Education, 2020)
Agricultural activities in developing countries are critical for the future of the world’s food security. These countries have the lowest agricultural productivity and dissemination of agricultural technologies are often insufficient. Extension has a vital role in improving agricultural productivity. The Caribbean country of Haiti is one such case. In Haiti, agricultural technicians perform much of the extension field work. Agricultural technicians often have a diploma earned at a Technical, Vocational, Education and Training (TVET) school. However, not much is known about Haitian TVET schools, as little research has been conducted. This study explored the context for Haitian agricultural TVET. Individual interviews with four school directors and three teachers per school (12 total), as well as a student focus group in each school allowed to identify the ambiguous cultural value of agricultural TVET in Haiti. Results identified the cultural disregard for TVET through its stakeholders’ contempt for this sector as well as the government’s failure to support it appropriately. However, it was also found that TVET added value to the agricultural system both for its inherent qualities, and because of the reputation, competitiveness it creates for the graduates through the schools’ curricula, INFP recognition, and the networking experiences it facilitates notably with internships.
Keywords: TVET; Haitian; agriculture